2014
DOI: 10.1136/bmjopen-2014-005551
|View full text |Cite
|
Sign up to set email alerts
|

Service configuration, unit characteristics and variation in intervention rates in a national sample of obstetric units in England: an exploratory analysis

Abstract: ObjectivesTo explore whether service configuration and obstetric unit (OU) characteristics explain variation in OU intervention rates in ‘low-risk’ women.DesignEcological study using funnel plots to explore unit-level variations in adjusted intervention rates and simple linear regression, stratified by parity, to investigate possible associations between unit characteristics/configuration and adjusted intervention rates in planned OU births. Characteristics considered: OU size, presence of an alongside midwife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Birth in hospital with a concurrent increase in the medicalization of the birth process has resulted in an overuse of intrapartum interventions and a global rise in CS as “mode of birth” [ 117 ]. Therefore, place of birth may be a factor that is associated with maternal wellbeing and birth outcomes [ 118 ]. Healthy women who have the opportunity to birth in settings/facilities that offer sufficient space to stand/move around, have access to birth companions and the support of a midwife on a one-to-one basis, are associated with improved outcomes and fewer interventions [ 119 ].…”
Section: Best Practice Culture and Educationmentioning
confidence: 99%
“…Birth in hospital with a concurrent increase in the medicalization of the birth process has resulted in an overuse of intrapartum interventions and a global rise in CS as “mode of birth” [ 117 ]. Therefore, place of birth may be a factor that is associated with maternal wellbeing and birth outcomes [ 118 ]. Healthy women who have the opportunity to birth in settings/facilities that offer sufficient space to stand/move around, have access to birth companions and the support of a midwife on a one-to-one basis, are associated with improved outcomes and fewer interventions [ 119 ].…”
Section: Best Practice Culture and Educationmentioning
confidence: 99%
“…An exploratory analysis in England found that intervention rates were higher in planned obstetric unit births compared to births in midwife-led settings in areas where higher proportions of women planned birth in midwife-led settings. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…All the public maternity units are technically orientated and able to attend both high risk and low-risk births. This raises issues as to the dubious benefits of giving birth in mixed environments, as recent studies have shown positive health results when healthy women are treated in midwife-led units that are separated from conventional obstetric units [ 6 , 37 ].…”
Section: Discussionmentioning
confidence: 99%